Pregnancy-related healthcare utilization among women with multiple sclerosis - Mainguy, Marie; Le Page, Emmanuelle; Michel, Laure; Leray, Emmanuelle (Frontiers in Neurology, 2023)
Introduction Many studies have investigated pregnancy in women with multiple sclerosis (MS). However, no study has measured prenatal healthcare utilization in women with MS or adherence to follow-up recommendations to improve antenatal care quality. A better knowledge of the quality of antenatal care in women with MS would help identify and better support women with insufficient follow-up. Our objective was to measure the level of compliance to prenatal care recommendations in women with MS using data from the French National Health Insurance Database. Methods This retrospective cohort study included all pregnant women with MS who gave live birth in France between 2010 and 2015. Using the French National Health Insurance Database, follow-up visits with gynecologists, midwives, and general practitioners (GPs) were identified, as well as ultrasound exams and laboratory tests. Based on the Adequacy of Prenatal Care Use and Content and Timing of care in Pregnancy indices, a new tool adapted to the French recommendations was developed to measure and classify the antenatal care trajectory (adequate or inadequate). Explicative factors were identified using multivariate logistic regression models. A random effect was included because women may have had more than one pregnancy during the study period. Results In total, 4,804 women with MS (N = 5,448 pregnancies ending in live births) were included. When considering only visits with gynecologists/midwives, 2,277 pregnancies (41.8%) were considered adequate. When adding visits with GP, their number increased to 3,646 (66.9%). Multivariate models showed that multiple pregnancy and higher medical density were associated with better adherence to follow-up recommendations. Conversely, adherence was lower in 25–29-year-old and >40-year-old women, in women with very low income, and agricultural and self-employed workers. No visits, ultrasound exams, and laboratory tests were recorded in 87 pregnancies (1.6%). In 50% of pregnancies, women had at least one visit with a neurologist during the pregnancy, and women restarted disease-modifying therapy (DMT) within 6 months after delivery in 45.9% of pregnancies. Discussion Many women consulted their GP during pregnancy. This could be linked to a low density of gynecologists but may also reflect the preferences of women. Our findings can help adapt recommendations and healthcare providers' practices according to the women's profiles.